2012
DOI: 10.1007/s00330-012-2475-5
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of prostate cancer extracapsular extension with high spatial resolution dynamic contrast-enhanced 3-T MRI

Abstract: Objectives To assess the value of dynamic contrast-enhanced (DCE) combined with T2-weighted (T2W) endorectal coil (ERC) magnetic resonance imaging (MRI) at 3 T (3T) for determining extracapsular extension (ECE) of prostate cancer. Methods In this IRB-approved study, ERC 3T MRI of the prostate was performed in 108 patients prior to radical prostatectomy. T2W fast spin-echo and DCE 3D gradient echo images were acquired. The interpretations of readers with varied experience were analyzed. MRI-based staging resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 63 publications
2
39
0
1
Order By: Relevance
“…[14][15][16][17] MpMRI interpretation is based on Prostate Imaging and Reporting Archiving Data System version 2 (PI-RADS v2) [18] , introduced to improve standardization of MRI interpretation by reporting suspicion scores (1-to 5-point scale based on fixed criteria) to provide clinical management guideline for suspicious PCa.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] MpMRI interpretation is based on Prostate Imaging and Reporting Archiving Data System version 2 (PI-RADS v2) [18] , introduced to improve standardization of MRI interpretation by reporting suspicion scores (1-to 5-point scale based on fixed criteria) to provide clinical management guideline for suspicious PCa.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings suggest that the negative predictive value for ECE with 1.5T MRI is inadequate to safely triage patients for nerve-sparing radical prostatectomy, as a large percentage of these patients may in reality have extra-capsular disease. It is important to note that since our data extraction period, we have transitioned to the use of 3T MRI, which we anticipate will increase the diagnostic accuracy of MRI for ECE and SVI as has been previously shown [12] . The next phase of our study will include collection of data for patients who underwent 3T prostate MRI to determine whether this change alone results in any differences in the predictive value of MRI in the evaluation of T3 prostate cancer.…”
Section: Discussionmentioning
confidence: 96%
“…The utilization of different MRI imaging techniques may have contributed to the wide variability in reporting the sensitivity, specificity, and predictive values of MRI for staging purposes [10] . The ability of MRI to detect ECE has been reported with sensitivities ranging between 23 to 91% and specificities ranging between 84 to 97% [11][12][13] . One study reported a positive predictive value of 79% and a negative predictive value of 91% for ECE with 3T MRI with ER coil [12] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11] MRI has been utilized to diagnose and stage PC. [11][12][13] reported a 13%-95% sensitivity and a 49%-97% specificity for MRI in the detection of extracapsular extension (ECE). [9] Developments in MRI technology improved tumor localization and detection of ECE.…”
Section: Discussionmentioning
confidence: 99%